LECTURE AS A FORM OF CHEMICAL KNOWLEDGE TRANSFER EDUCATORS - Карпенко, Юлія; Балицька, Аліна (SWorldJournal, 2025)
The article examines the effectiveness of lectures as a leading method for delivering chemical knowledge to higher medical education students, particularly in disciplines such as "Medical Chemistry" and "General and Inorganic Chemistry." The author analy